Monday is wash day - Sundby, MaryAnn (Ripple Grove Press, 2016)
"In this timeless story from a time not so long ago, Annie and her sister help Mama with washing the clothes on Monday morning. From gathering and sorting the clothes, to washing and hanging them outside to dry, to folding and putting them away, the family works together to get the job done."--Amazon.com